Petrogenesis of mafic-intermediate magmatism of the Michoacán–Guanajuato volcanic field in Western Mexico. A geochemical review - Torres-Sánchez, Darío; Sosa-Ceballos, Giovanni; Bolós, Xavier; Macías, José Luis (Frontiers in Earth Science, 2022)
The Michoacán-Guanajuato volcanic field (MGVF) in the western Trans-Mexican Volcanic Belt is one of the largest and most diverse monogenetic volcanic fields in the world holding more than 1200 volcanic vents. Its eruptive activity goes back to 7 Ma, it is considered an active volcanic field and the composition of its rocks varies from mafic to silicic. It is essential to understand the geochemical evolution of its products, the complex petrogenetic processes and the origin of magmas in central Mexico. Although these processes are linked to the subduction of the Cocos plate beneath the North American plate, the magmatic plumbing system of the MGVF remains not completely understood. The MGVF has been studied for decades, focusing in its dominant intermediate magmas. Nevertheless, the origin and evolution of the mafic components and their relation with the intermediate rocks have been poorly discussed. Here, we compile geological and geochemical data of the MGVF to discuss the petrogenesis of mafic magmas along the volcanic field and the role they play in the generation of intermediate melts. We used data published for 429 samples of mafic and intermediate volcanic rocks. Conventional procedures and statistical techniques were used to process the dataset. We propose that MGVF mafic magmas are derived from low degrees (~1-15%) of partial melting of a spinel-lherzolite bearing source/mantle related to the rapid ascent of the asthenosphere caused by an extensional regime that is present in the area. In contrast, intermediate magmas where divided into two main groups based in the Mg content, high-Mg intermediate rocks, which seems to be derived from different rates of assimilation and fractional crystallization process, and low-Mg intermediate rocks which can be related to fractional crystallization of mafic magmas. Additionally, mafic and intermediate magmas display a chemical diversity which are related to mantle heterogeneity that domains in the mantle wedge.